The well-being of older age Lithuanians: Policy implications - Kairys, Antanas; Zamalijeva, Olga; Bagdonas, Albinas; Eimontas, Jonas; Pakalniškienė, Vilmantė; Sadauskaitė, Raimonda (Psichologija, 2021)
Many countries of the world consider the well-being of citizens to be one of their most important goals. Nowadays there is a growing concern about the well-being of older people. Considering the aging population, there is a call for social policies aimed at strengthening the well-being of older people. Therefore, recommendations were prepared for policymakers on possible ways to strengthen the well-being of the older age Lithuanian population. The recommendations are based on data from the 7th wave of the Survey of Health, Aging, and Retirement in Europe (SHARE). There were 2014 persons aged 50 and older interviewed in Lithuania in the 7th wave of the SHARE survey. Data on various aspects of well-being, health, work and economic situation, childhood circumstances, experiences of discrimination were analyzed. Based on different aspects of well-being it was found, that respondents can be grouped into high, low, and medium well-being clusters, moreover the analysis showed that the Lithuanian population has relatively low well-being compared to other countries. Recommendations were formulated covering possible measures for chronic diseases, co-morbid mental health disorders, work, economic situation, childhood environment, and personal life history. The recommendations are addressed to health, social and employment, education, and science policymakers.